Our man in tokyo eaudiobook An american ambassador and the countdown to pearl harbor. - Kemper, Steve (HarperAudio, 2022)
A gripping, behind-the-scenes account of the personalities and contending forces in Tokyo during the volatile decade that led to World War II, as seen through the eyes of the American ambassador who attempted to stop the slide to war. In 1932, Japan was in crisis. Naval officers had assassinated the prime minister and conspiracies flourished. The military had a stranglehold on the government. War with Russia loomed, and propaganda campaigns swept the country, urging schoolchildren to give money to procure planes and tanks. Into this maelstrom stepped Joseph C. Grew, America's most experienced and talented diplomat. When Grew was appointed ambassador to Japan, not only was the country in turmoil, its relationship with America was rapidly deteriorating. For the next decade, Grew attempted to warn American leaders about the risks of Japan's raging nationalism and rising militarism, while also trying to stabilize Tokyo's increasingly erratic and volatile foreign policy. From domestic terrorism by Japanese extremists to the global rise of Hitler and the fateful attack on Pearl Harbor, the events that unfolded during Grew's tenure proved to be pivotal for Japan, and for the world. His dispatches from the darkening heart of the Japanese empire would prove prescient—for his time, and for our own. Drawing on Grew's diary of his time in Tokyo as well as U.S. embassy correspondence, diplomatic dispatches, and firsthand Japanese accounts, Our Man in Tokyo brings to life a man who risked everything to avert another world war, the country where he staked it all—and the abyss that swallowed it. Supplemental enhancement PDF accompanies the audiobook.